Romper el silencio: una aproximación crítica a la regulación del arresto domiciliario - Czarny, Maia (2022)
What does the law say with its silences? How are power relations hidden and/or reproduced through (hetero)normative language? In this essay it is intended to rehearse some answers to these questions, in the light of the legalphilosophical analysis of the normative assumption that foresees the possibility that - only - the mother in charge of her child under five years of age, or of a person with disabilities, has access to the benefit of house arrest (article 10 of the Criminal Code and 32 of the Penal Enforcement Law, both in subsection "F"). Based on the factual and case-law background, as well as the contributions of some authors inserted in the critical current of law - Entelman, Ruiz, Cárcova, Foucault, Ost, Bubnova, Gorali -, it is intended to elucidate the way in which the paradoxical function of law operates there. What is in principle a positive action in favor of historically over-vulnerated groups reproduces, in silence, certain mandates, typical of a functional structure of patriarchy. Without prejudice to the importance that it deserves to analyze that moment in which the law is said, the re-reading and therefore, the possible re-writing of this legislative technique, through a legal reform, appears as an ideal tool to give a more comprehensive response to structural conflict